Artificial Intelligence Can Improve Patient Management at the Time of a Pandemic: The Role of Voice Technology - Jadczyk, Tomasz; Wojakowski, Wojciech; Tendera, Michal; Henry, Timothy D; Egnaczyk, Gregory; Shreenivas, Satya (JMIR. Journal of medical internet research, 2021)
Artificial intelligence-driven voice technology deployed on mobile phones and smart speakers has the potential to improve patient management and organizational workflow. Voice chatbots have been already implemented in health care-leveraging innovative telehealth solutions during the COVID-19 pandemic. They allow for automatic acute care triaging and chronic disease management, including remote monitoring, preventive care, patient intake, and referral assistance. This paper focuses on the current clinical needs and applications of artificial intelligence-driven voice chatbots to drive operational effectiveness and improve patient experience and outcomes.
Keywords: Telemedicine; software pro rozpoznávání řeči; konziliární vyšetření a konzultace; Referral and Consultation; komunikace; lidé; péče o pacienty v kritickém stavu; umělá inteligence; telemedicína; Communication; COVID-19; Critical Care; mobilní telefon; pandemie; Triage; poskytování zdravotní péče; Delivery of Health Care; Cell Phone; Voice; Speech Recognition Software; chronická nemoc; třídění pacientů; Chronic Disease; Artificial Intelligence; Pandemics; hlas; Humans